Pain after emergency treatments of symptomatic irreversible pulpitis and symptomatic apical periodontitis in the permanent dentition: a systematic review of randomized clinical trials - Alhilou, Abdelrahman M.; Al-Moraissi, Essam Ahmed; Bakhsh, Abdulaziz; Christidis, Nikolaos; Näsman, Peggy (Frontiers in Oral Health, 2023)
Background Symptomatic irreversible pulpitis (SIP) or symptomatic apical periodontitis (SAP) are two painful conditions often warranting emergency treatment. The most common emergency treatments supported by evidence are pulpotomy and pulpectomy and are normally performed under time-constrained circumstances. However, there is no strong evidence of which treatment suggested in literature a clinician can use to reduce endodontic pain effectively. Therefore, the aim of this systematic review is to investigate the present knowledge on postoperative pain related to the two types of emergency treatments available for treating SIP and SAP. Methods Randomized controlled trials investigating postoperative pain after emergency treatments (pulpotomy and/or pulpectomy) on permanent dentition with signs and symptoms of SIP and/or SAP were searched in three major databases from 1978 until 2022. Risk of bias was assessed with Cochrane's tool. Results Only five studies fulfilled the inclusion criteria. The included studies indicated that pulpotomy and pulpectomy are both suitable treatment options for SAP and SIP, as they provide sufficient alleviation of pain in permanent dentition. However, inconsistent results were found between the included trials on which emergency treatment is more effective in reducing pain. Cochrane's tool revealed that the studies had a low risk of bias. Limitations found in the design of the included randomized control trials decreased the level of evidence. None of the included studies accounted for essential confounding variables, such as factors affecting pain (including the psychological aspects). Moreover, possible non-odontogenic pain was not assessed, and therefore, it was not excluded; hence, affecting the internal validity of the studies. Conclusion There are controversies within the available randomized control trials on which treatment is most effective in reducing emergency pain. This could be due to some weaknesses in the design of the clinical trials. Thus, further well-designed studies are warranted to draw conclusions on which emergency treatment is more effective in reducing pain. Systematic Review Registration PROSPERO (CRD42023422282).